Synchrotron Radiation X-ray Diffraction Techniques Applied to Insect Flight Muscle - Iwamoto, Hiroyuki (Int J Mol Sci, 2018)
X-ray fiber diffraction is a powerful tool used for investigating the molecular structure of muscle and its dynamics during contraction. This technique has been successfully applied not only to skeletal and cardiac muscles of vertebrates but also to insect flight muscle. Generally, insect flight muscle has a highly ordered structure and is often capable of high-frequency oscillations. The X-ray diffraction studies on muscle have been accelerated by the advent of 3rd-generation synchrotron radiation facilities, which can generate brilliant and highly oriented X-ray beams. This review focuses on some of the novel experiments done on insect flight muscle by using synchrotron radiation X-rays. These include diffraction recordings from single myofibrils within a flight muscle fiber by using X-ray microbeams and high-speed diffraction recordings from the flight muscle during the wing-beat of live insects. These experiments have provided information about the molecular structure and dynamic function of flight muscle in unprecedented detail. Future directions of X-ray diffraction studies on muscle are also discussed.